Middeleeuse ampsperspektiewe en die ontwikkeling van die Protestantse versetleer in die sestiende eeuse Duitse politieke denke, 1531 - 1550 - Raath, Andries (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2023)
Manegold of Lautenbach’s tract Liber ad Gebehardum (c. 1085) was a response to the excommunication of Henry IV by Gregory VII. Under the heading Quod rex non sit nomen nature, sed vocabulum officii, Manegold considers the issue of kingship, tyranny and resistance to oppression. Manegold maintains that although all honour is due to the office of king, kingship, like ecclesiastical powers is only the name of an office. When the person appointed to a specific office is put out of office, he is no longer what he was, and the honour due to the office is not to be paid to him. Whoever pays him the reverence due to his lost office is rather a transgressor than the keeper of the laws; whereas if he commands that which is against the Lord, he is by no means to be obeyed, but rather to be resisted with all freedom. The apostle who bade all to obey the powers, chose rather to die than yield to Nero, thus teaching us by his example that when we cannot obey God and the secular power, we should obey God rather than men. Manegold’s emphasis on the powers of rulers attached to their respective political offices and not to their persons, resounded through the history of political thought. Some of his ideas surfaced in the Lutheran struggle against tyranny. Justus Menius (1499-1558) advanced the notion that self-defense is a form of legitimate resistance to the exercise of tyrannical power by political rulers. His views together with those of Manegold and other Medieval authors shaped the contents of the Magdeburg Confession (1550). By the time the Confession was drafted, Nicolaus von Amsdorff (1483-1565) and other Lutheran pastors had linked the duty to resist tyrannical rulers to the idea of office – thereby drafting the outlines of a doctrine that served as a platform for resisting rulers exceeding the limits of their political authority.